A study of the factors which affect the quality of working life (QWL) among employees in healthcare industry / Norsyahida Mohd Maamon - Mohd Maamon, Norsyahida (2014)
Employee is an asset for organization that helps organization to be successful and achieve its organizational objectives, thus it is imperative for the organization to ensure that employees are experienced quality of working life. The objective of this study is to examine the three factors, work autonomy, communication and supervisory and emotional support on quality of working life (QWL) among employees in healthcare industry. Data were collected from 375 employees from two hospitals and three health clinics that located in Pahang. Variables were measured used Statistical Package for the Social Science (SPSS). Then, correlation and regression were used to test the hypothesis. The findings have shown that work autonomy, communication and supervisory and emotional support are correlated with quality of working life; with supervisory and emotional support was the most influential factor that contributes to QWL. Therefore, it can be said that an organization needs to practise and increase work autonomy, communication and supervisory emotional support to improve QWL. Improving QWL is important as it contributes to employees’ productivity and commitment.